Campur Kode Dalam Video Blog Channel Youtube Erikacang - Ranti Octhalia; Meira Anggia Putri (Universitas Negeri Padang, 2021)
Code mixing is a phenomenon that can be encountered in everyday life, but there are still many who do not realize that when communicate, sometimes we do code mixing. Youtube is a video-based social media that has social interactions in it. One type of video found on YouTube is a video blog and we can found code mixing on several video blogs. This study aims to describe the forms and causes of code mixing on the Erikacang YouTube video blog channel. This type of research is qualitative research with descriptive methods. In this study, 17 data were found in the mixed code in the form of insertion, 28 mixed code for alternation forms, and one data for the form of congruent lexicalization. Meanwhile the findings of the cause of code mixing were 32 data caused by the habits of the speakers, three data was caused by there are no proper words in the used language, and 11 data because the speaker wanted to show off his learning or position.